Women's psychological experiences of physiological childbirth: a meta-synthesis. Issue 10 (18th October 2018) - Olza, Ibone; Leahy-Warren, Patricia; Benyamini, Yael; Kazmierczak, Maria; Karlsdottir, Sigfridur Inga; Spyridou, Andria; Crespo-Mirasol, Esther; Takács, Lea; Hall, Priscilla J; Murphy, Margaret; Jonsdottir, Sigridur Sia; Downe, Soo; et al.
Abstract : Objective: To synthesise qualitative studies on women's psychological experiences of physiological childbirth. Design: Meta-synthesis. Methods: Studies exploring women's psychological experiences of physiological birth using qualitative methods were eligible. The research group searched the following databases: MEDLINE, CINAHL, PsycINFO, PsycARTICLES, SocINDEX and Psychology and Behavioural Sciences Collection. We contacted the key authors searched reference lists of the collected articles. Quality assessment was done independently using the Critical Appraisal Skills Programme (CASP) checklist. Studies were synthesised using techniques of meta-ethnography. Results: Eight studies involving 94 women were included. Three third order interpretations were identified: 'maintaining self-confidence in early labour', 'withdrawing within as labour intensifies' and 'the uniqueness of the birth experience'. Using the first, second and third order interpretations, a line of argument developed that demonstrated 'the empowering journey of giving birth' encompassing the various emotions, thoughts and behaviours that women experience during birth. Conclusion: Giving birth physiologically is an intense and transformative psychological experience that generates a sense of empowerment. The benefits of this process can be maximised through physical, emotional and social support for women, enhancing their belief in their ability to birth and not disturbing physiology unless it is necessary. Healthcare professionals need to take cognisance of the empowering effects of the psychological experience of physiological childbirth. Further research to validate the results from this study is necessary. PROSPERO registration number: CRD42016037072.